2001
DOI: 10.1034/j.1600-051x.2001.280809.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal salts on the oral production of volatile sulfur‐containing compounds (VSC)

Abstract: Apart from Hg2+ and Cu2+, the metals had a significantly greater effect on H2S than on CH3SH. Cu2+ and Hg2+ have well-known antibacterial activity and may presumably also operate by this mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 13 publications
1
80
0
6
Order By: Relevance
“…Nonetheless, cupric chloride is the most effective metal solution for inhibiting hydrogen sulfide production at 1, 2 and 3 h after rinsing. 60 Zinc is the metal ion of choice with this purpose because of its low toxicity and its other favorable properties, such as not causing dental staining. It is known that zinc ions possessing anti-VSC effects have affinity for sulfur, forming sulfides with low solubility.…”
Section: Zincmentioning
confidence: 99%
“…Nonetheless, cupric chloride is the most effective metal solution for inhibiting hydrogen sulfide production at 1, 2 and 3 h after rinsing. 60 Zinc is the metal ion of choice with this purpose because of its low toxicity and its other favorable properties, such as not causing dental staining. It is known that zinc ions possessing anti-VSC effects have affinity for sulfur, forming sulfides with low solubility.…”
Section: Zincmentioning
confidence: 99%
“…When methyl mercaptan is produced by the degradation of methionine, dimethyl sulfide is produced from methyl mercaptan. The process of protein degradation by proteolytic enzymes of bacterial origin could be inhibited by zinc ions which has been shown previously 10,11) . As well as zinc ion, effect and ease of mouth rinse are useful, enough time is considered in the treatment of oral hygiene 5) .…”
Section: Discussionmentioning
confidence: 83%
“…Although VSC is one of the important elements essential for biological function, its intake must be maintained properly because an excess may also cause a disease. In a study with a purpose of suppressing halitosis, zinc chloride concentrations of 0.5% 8) , 0.2% 9) , 0.1% 10) have been reported so far. There is no report such as hypersensitivity as to its side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of zinc chloride on halitosis has been identified in many basic clinical studies [4][5][6] . Recently, we reported that bismuth oxychloride, which is widely used as a synthetic pearl essence in cosmetics, is an effective VSC inhibitor 7) .…”
Section: Introductionmentioning
confidence: 99%